2004
DOI: 10.1152/ajpendo.00514.2003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hyperosmolality stimulates leptin secretion acutely by a vasopressin-adrenal mechanism

Abstract: Levy, James R., and Wayne Stevens. Plasma hyperosmolality stimulates leptin secretion acutely by a vasopressin-adrenal mechanism. Am J Physiol Endocrinol Metab 287: E263-E268, 2004. First published April 6, 2004; 10.1152/ajpendo.00514.2003.-Glucose administration to rodents acutely stimulates leptin secretion. To investigate the mechanism, rats were infused intravenously with various concentrations of glucose, and plasma leptin concentrations were measured with time. The osmolality of the infusates was equaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…An increase in serum osmolarity by salt has been shown to activate the aldose reductase-fructokinase pathway in the liver and hypothalamus that can over time lead to metabolic syndrome and elevations in blood pressure [3]. The increase in serum and SNS osmolarity stimulates vasopressin and leptin release [34], and the latter can activate the SNS sympathetic response to raise blood pressure [35]. An increase in SNS osmolarity also stimulates the production of cardiotonic steroids (Na-K ATPase) inhibitors that cause peripheral vasoconstriction [36].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in serum osmolarity by salt has been shown to activate the aldose reductase-fructokinase pathway in the liver and hypothalamus that can over time lead to metabolic syndrome and elevations in blood pressure [3]. The increase in serum and SNS osmolarity stimulates vasopressin and leptin release [34], and the latter can activate the SNS sympathetic response to raise blood pressure [35]. An increase in SNS osmolarity also stimulates the production of cardiotonic steroids (Na-K ATPase) inhibitors that cause peripheral vasoconstriction [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, this contribution is exaggerated with mannitol, since it remains in the vasculature with a half-life of ∼60 minutes. 22 The osmolality-induced Δ R 1ρ for glucoCESL is dependent on the difference between blood and tissue glucose concentrations. Tissue uptake of Glc and 2DG makes their osmolality contributions to Δ R 1ρ even smaller, since there will be rapid equilibration of blood and tissue glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Next, glucoCESL responses were compared for matched doses of Glc, 2DG, and mannitol, and with measurement of arterial blood Glc and 2DG levels. The latter studies served to characterize dynamic properties and to assess Δ R 1ρ contributions from changes in tissue water content after intravenous injection of hypertonic solutions; mannitol served as a control, since it induces large elevations in plasma osmolality, has a long half-life in blood (∼60 minutes in rats 22 ), and does not cross the blood–brain barrier. 23 And lastly, glucoCESL responses were obtained for varied SL power levels at steady-state blood glucose levels to further examine the origin and quantification of glucoCESL responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that, in rats with chronic mild volume expansion induced by drinking 1% saline, blockade of endogenous leptin with a specific antibody decreases diuresis and natriuresis by 15-20%, suggesting that the renal effect of leptin may be relevant for maintaining Na þ balance [57,60]. In addition, leptin expression in adipose tissue increases in response to a high-salt diet [61] or intravenous infusion of hypertonic NaCl [62] and decreases on low-salt diet [63], as expected for a mediator regulating Na þ balance.…”
Section: Renal Effect Of Leptinmentioning
confidence: 99%